MicroRNA397b negatively regulates resistance of Malus hupehensis to Botryosphaeria dothidea by modulating MhLAC7 involved in lignin biosynthesis. (March 2020) - Yu, Xinyi; Gong, Hongyong; Cao, Lifang; Hou, Yingjun; Qu, Shenchun
Highlights: Mh-miR397 are induced by Botryosphaeria dothidea infection. Mh-miR397 target to MhLAC7 by directly cleavage. Mh-miR397b reduced the resistance of N. benthamiana to B. cinerea . Mh-miR397b plays a negative role of Malus resistance to B. dothidea . Mh-miR397b may involve in lignin biosynthesis by modulating Malus LAC7 expression. Abstract: MicroRNA (miRNA)-mediated post-transcriptional regulation plays a vital role in the response of plants to pathogens. Although the microRNA397 family has been implicated in physiological processes as an important regulator, little is known about its function in the resistance of plants to pathogens. Here, Malus hupehensis miR397, which was induced by Botryosphaeria dothidea infection, was identified to directly target M. hupehensis Laccase7 ( MhLAC7 ). The expression analysis of mature Mh-miR397 and MhLAC7 revealed their partly opposite expression patterns. The coexpression of Mh-miR397b in MhLAC7 overexpressing Nicotiana benthamiana suppressed the accumulation of exogenous MhLAC7 and endogenous NbLAC7, which led to decreased lignin content and reduced plant resistance to Botrytis cinerea . As reflected by increasing disease severity and pathogen growth, overexpression of miR397b in both the resistant M. hupehensis and susceptible M. domestica 'Gala' resulted in an increased sensitivity to B. dothidea infection, owing to reduced LAC7 expression and lignin content; however, the inhibition of miR397 had opposite effects. MicroRNA397 functions as a negative regulator in the resistance of Malus to B. dothidea by modulating the LAC7 expression and lignin biosynthesis.